Antimicrobial resistance and biofilm formation potential of enterotoxigenic Staphylococcus aureus and Escherichia coli from cutting board surfaces - Isa, Shu'aibu (2019)
Survival of multidrug resistant enterotoxigenic S. aureus and E. coli with biofilm forming potential (BFP) in commercial food premises is a possible danger to the health of consumers especially in societies where most of the population depend on these premises for their daily meals. These organisms can serve as sources of outbreaks leading to morbidity and mortality particularly in persons with compromised immunity. Isolates obtained from selected food premises in Selangor Malaysia were subjected to Gram’s staining and various biochemical identifications and later confirmed by polymerase chain reaction (PCR) using specific primers. Antimicrobial susceptibility testing was conducted to ascertain the multidrug resistant (MDR) isolates and PCR was undertaken using the primers for the genes of most widespread toxins implicated in food poisoning outbreaks as staphylococcal enterotoxin (SE) A and D as well as heat-labile (LT) and heat-stable enterotoxin genes of E. coli. The MDR and non-MDR isolates were further subjected to biofilm formation.The MDR isolates of both S. aureus and E. coli with strong BFP were challenged with chemical sanitizers, peracetic acid (PAA), sodium hypochlorite (NaOCl) and benzalkonium chloride (BAC) using minimum biofilm eradication concentration (MBEC) device to determine the sessile minimum inhibitory concentration (SMIC) and MBEC. Cutting boards similar in chemical composition (polyethylene) to those used in the food premises were contaminated with both MDR and non-MDR isolates with strong BFP and tested with the sanitizers and hot water at various concentrations and temperatures respectively, at various times of contact. Twenty four isolates were confirmed to be S. aureus and also 24 were confirmed to be E. coli. All the S. aureus isolates (100%) possess the SEA and SED genes while only 37.5% (n=9) of the confirmed E. coli possessed LT genes. The MDR and non-MDR S. aureus isolates were 87.5% (n=21) while 66.7% (n=16) were the non- MDR E. coli and 57% (n=12) of the MDR and non-MDR S. aureus had strong BFP while 75% (n=12) of the non-MDR E. coli had strong BFP. PAA proved to be the most effective of all the sanitizers although there were resistance by isolates tagged SA016 and SA022 of the S. aureus. Hot water had higher activity than the sanitizers and there was still resistance by SA016. On the cutting boards, the results of the sanitizers action was promising with PAA being significantly higher (P<0.05) in activity than the rest of the sanitizers. Hot water had the highest activity even at smaller contact time of antimicrobial action than the sanitizers reducing the logarithmic counts of the strongest biofilm forming isolates by 5.05 Log CFU/ 10 cm2. All isolates were reduced to acceptable limits or totally eliminated by the sanitizers at 5 min and 10 min contact times. The findings in this study will give suggestions on the appropriate sanitizing agents and their concentrations to be used on cutting boards and other food contact surfaces for sanitization so as to reduce the risk/incidence of outbreaks due to these organisms.